Ecologizing education nature-centered teaching for cultural change - Blenkinsop, Sean (Cornell University Press, 2024)
Ecologizing Education explores how we can reenvision education to meet the demands of an unjust and rapidly changing world. Going beyond "green" schooling programs that aim only to shape behavior, Sean Blenkinsop and Estella Kuchta advance a pedagogical approach that seeks to instills eco-conscious and socially just change at the cultural level. Ecologizing education, as this approach is called, involves identifying and working to overcome anti-ecological features of contemporary education. This approach, called ecologizing education, aims to develop a classroom culture in sync with the more-than-human world where diversity and interdependency are intrinsic.Blenkinsop and Kuchta illustrate this educational paradigm shift through the real-world stories of two public elementary schools located in British Columbia. They show that this approach to learning starts with recognizing the environmental and social injustices that pervade our industrialized societies. By documenting how ecologizing education helps children create new relationships with the natural world and move toward mutual healing, Blenkinsop and Kuchta offer a roadmap for what may be the most potent chance we have at meaningful change in the face of myriad climate crises. Timely, practical, and ultimately inspirational, Ecologizing Education is vital reading for any parent, caregiver, environmentalist, or educator looking for wholistic education that places nature and the environment front and center